EGFR internal tandem duplications in fusion‐negative congenital and neonatal spindle cell tumors. Issue 1 (25th July 2022) - Koo, Selene C.; Schieffer, Kathleen M.; Lee, Kristy; Gupta, Ajay; Pfau, Ruthann B.; Avenarius, Matthew R.; Stonerock, Eileen; LaHaye, Stephanie; Fitch, James; Setty, Bhuvana A.; Roberts, Ryan; Ranalli, Mark; et al.
Abstract: Next‐generation sequencing (NGS) assays can sensitively detect somatic variation, and increasingly can enable the identification of complex structural rearrangements. A subset of infantile spindle cell sarcomas, particularly congenital mesoblastic nephromas with classic or mixed histology, have structural rearrangement in the form of internal tandem duplications (ITD) involving EGFR . We performed prospective analysis to identify EGFR ITD through clinical or research studies, as well as retrospective analysis to quantify the frequency of EGFR ITD in pediatric sarcomas. Within our institution, three tumors with EGFR ITD were prospectively identified, all occurring in patients less than 1 year of age at diagnosis, including two renal tumors and one mediastinal soft tissue tumor. These three cases exhibited both cellular and mixed cellular and classic histology. All patients had no evidence of disease progression off therapy, despite incomplete resection. To extend our analysis and quantify the frequency of EGFR ITD in pediatric sarcomas, we retrospectively analyzed a cohort of tumors ( n  = 90) that were previously negative for clinical RT‐PCR‐based fusion testing. We identified EGFR ITD in three analyzed cases, all in patients less than 1 year of age ( n  = 18; 3/18, 17%). Here we expand the spectrum of tumors with EGFR ITD to congenital soft tissue tumors and report an unusual example of an EGFR ITD in a tumor with cellular congenital mesoblastic nephroma histology. We also highlight the importance of appropriate test selection and bioinformatic analysis for identification of this genomic alteration that is unexpectedly common in congenital and infantile spindle cell tumors.